Reconsidering Boundaries: Human Resource Management in a Networked World. Issue 2 (21st January 2014) - Swart, Juani; Kinnie, Nicholas; Townsend, Keith; Wilkinson, Adrian
Abstract In the twenty‐first century, work activities tend to span organizational boundaries and take place in projects or networks. This cross‐boundary working has major implications for current HRM models that are more suited to an industrial economy, which assumes a single employer and where work is carried out within a set of clearly defined boundaries. We draw on a decade of empirical research in cross‐boundary contexts to identify: (1) three types of networks (interactive, interwoven, and integrated) that vary according to their boundary properties, the focus of the work activity, and the prominent identification; (2) the particular structural, relational, and knowledge‐based tensions (Phelps, Heidl, & Wadhwa, 2012) that are inherent in each networked context; and (3) three HRM models (buffering, borrowing, and balancing) that are appropriate to sustain networked working in these contexts. The main contribution of the article is the identification of HRM models in networked contexts. © 2014 Wiley Periodicals, Inc.